A Find of Roman Stucco Work at the Capitolium of Roman Iader (Archaeologia Adriatica, 2008)
During renovation of the building of the Theological Seminary in Zadar rescue archaeological excavations were carried out at the end of 1992 and in March 1993 in the courtyard. The position of the courtyard makes it the central part of the large complex of the Theological Seminary, with its façade located opposite the portal of the Zadar Cathedral. Its length extends along the perimeter wall on the northeastern side of the Roman capitolium (or temple precinct), which on this lateral side because of leveling of the plateau was built of massive blocks in the opus quadratum technique with emphasized central protrusions.
Keywords: Iader; capitolium,; stucco work